2021
DOI: 10.1038/s41598-021-89676-5
|View full text |Cite
|
Sign up to set email alerts
|

An open-source semi-automated robotics pipeline for embryo immunohistochemistry

Abstract: A significant challenge for developmental systems biology is balancing throughput with controlled conditions that minimize experimental artifacts. Large-scale developmental screens such as unbiased mutagenesis surveys have been limited in their applicability to embryonic systems, as the technologies for quantifying precise expression patterns in whole animals has not kept pace with other sequencing-based technologies. Here, we outline an open-source semi-automated pipeline to chemically fixate, stain, and 3D-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…The number of lines/embryos analyzed for each case are indicated in figure legends. For analyzing E3N mutant lines, 98 individual nuclei were identified using the automated threshold algorithm on ImageJ and a watershed to split large ROIs; average intensities for each nucleus were measured. For analyzing eveS2 mutant lines, we used ImageJ to perform Z-projections of max intensity, and a MATLAB (version R2018b; The MathWorks, Inc.) automated image analysis pipeline ( Data S1 ) was developed to capture expression signal along the AP axis on stage 5 embryos.…”
Section: Methodsmentioning
confidence: 99%
“…The number of lines/embryos analyzed for each case are indicated in figure legends. For analyzing E3N mutant lines, 98 individual nuclei were identified using the automated threshold algorithm on ImageJ and a watershed to split large ROIs; average intensities for each nucleus were measured. For analyzing eveS2 mutant lines, we used ImageJ to perform Z-projections of max intensity, and a MATLAB (version R2018b; The MathWorks, Inc.) automated image analysis pipeline ( Data S1 ) was developed to capture expression signal along the AP axis on stage 5 embryos.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, this opens the avenue towards fast and cost-efficient metabolic phenotyping at a population scale. Our general approach, combined with advances in robotics 41,42 and automated behavioral characterization 43 , could turn phenomics into a standardizable phenotyping method for multiple fields of biological research.…”
Section: Discussionmentioning
confidence: 99%
“…1l, 2k, 3g, 5i), images were analyzed in ImageJ: a circular ROI of constant size was used to measure average intensity across the different regions (selected as shown in figures); number of lines/embryos analysed for each case are indicated in figure legends. For analyzing E3N mutant lines (Fuqua et al, 2021), individual nuclei were identified using the automated threshold algorithm on ImageJ and a watershed to split large ROIs; average intensities for each nucleus were measured. For analyzing eveS2 mutant lines, we used ImageJ to perform Z-projections of max intensity, and a MATLAB (version R2018b; The MathWorks, Inc.) automated image analysis pipeline (named Script-GAC ) was developed to capture expression signal along the AP axis on stage 5 embryos.…”
Section: Methodsmentioning
confidence: 99%